Environmental Monitoring Using IoT - Shaikh Junaid Ahmad (Journal Electrical and Computer Experiences, 2023)
The Internet of Things (IoT) has revolutionized the way we collect and analyze data, particularly in the field of environmental monitoring. By using sensors and other IoT devices, it is possible to collect real-time data on a variety of environmental factors, such as temperature, air quality, water quality, and more. This data can then be analyzed to identify patterns and trends, and to make more informed decisions about how to manage and protect our environment. In this abstract, we explore the applications and benefits of environmental monitoring using IoT, including improved decision-making, increased efficiency, and reduced costs. We also discuss some of the challenges associated with IoT-based environmental monitoring, such as data security and privacy concerns, and the need for standardized protocols and frameworks. Overall, IoT-based environmental monitoring represents a promising new frontier in environmental management, with the potential to transform the way we understand and protect our planet.